End-to-end test of an online adaptive treatment procedure in MR-guided radiotherapy using a phantom with anthropomorphic structures - Elter, Alina; Dorsch, Stefan; Mann, Philipp; Runz, Armin; Johnen, Wibke; Renkamp, Claudia Katharina; Klüter, Sebastian; Karger, Christian (Physics in medicine and biology, 2019)
Online adaptive treatment procedures in magnetic resonance (MR)-guided radiotherapy (MRgRT) allow compensating for inter-fractional anatomical variations in the patient. Clinical implementation of these procedures, however, requires specific end-to-end tests to validate the treatment chain including imaging, treatment planning, positioning, treatment plan adaption and accurate dose delivery. For this purpose, a new phantom with reproducibly adjustable anthropomorphic structures has been developed. These structures can be filled either with contrast materials providing anthropomorphic image contrast in MR and CT or with polymer dosimetry gel (PG) allowing for 3D dose measurements. To test an adaptive workflow at a 0.35 T MR-Linac, the phantom was employed in two settings simulating inter-fractional anatomical variations within the patient. The settings included two PG-filled structures representing a tumour and an adjacent organ at risk (OAR) as well as five additional structures. After generating a treatment plan, three irradiation experiments were performed: (i) delivering the treatment plan to the phantom in reference setting, (ii) delivering the treatment plan after changing the phantom to a displaced setting without adaption, and (iii) adapting the treatment plan online to the new setting and delivering it to the phantom. PG measurements revealed a homogeneous tumour coverage and OAR sparing for experiment (i) and a significant under-dosage in the PTV (down to 45% of the prescribed dose) and over-dosage in the OAR (up to 180% relative to the planned dose) in experiment (ii). In experiment (iii), a uniform dose in the PTV and a significantly reduced dose in the OAR was obtained, well-comparable to that of experiment (i) where no adaption of the treatment plan was necessary. PG measurements were well comparable with the corresponding treatment plan in all irradiation experiments. The developed phantom can be used to perform end-to-end tests of online adaptive treatment procedures at MR-Linac devices before introducing them to patients.